PENGUJIAN STABILITAS DAN MUTU FISIK LIPSTIK DARI EKSTRAK UMBI WORTEL (Daucus carota L.) - Lutsina, Novi Winda; Kristyanti, Yulia; More, Evanisia (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Lipstick is a cosmetic preparation used to color lips with an artistic touch so as to give an aesthetic impression in cosmetology. The dyes used in lipstick preparations must be paid attention to because they are very likely to be ingested with saliva or the food and drinks consumed, for this reason, it must be ensured that lipstick dyes are made from natural dyes and are not dangerous. Carrots are one of the natural ingredients as a source of antioxidants because they contain the active compound β-carotene which has an intensity of orange to orange color. The purpose of this research is to formulate lipstick from natural carrot root dyes. The extraction method used in this study was carrot root extract obtained from carrot powder maceration with a solvent ratio of methanol and n-hexane. Lipstick formulations were made into 3 kinds of formulations with each extract concentration of 0% in formula I, 5% in formula II, and 10% in formula III. Each lipstick formula was tested for physical quality including an organoleptic test, smear test, melting point test, pH test, and stability test. The results of this study indicate that the color of the lipstick produced in carrot root extract is dark orange-orange. This orange color can come from carrot root juice which can be used as a natural dye. The results of the stability test of the preparations showed that all formulations had a good shape, remained hard, not soft, and not runny or slimy. Formulation II is the formulation with the best stability because at a concentration of 10% carrot root extract the shape is good, not watery, the hardness level does not decrease and it is not easily broken.